Training programs evaluation for educational supervisors in Oman - Al-Hosni, Z.A.K.; Hoque, K.E.; Idris, A.R.; Othman, Abdul Jalil (Macrothink Institute, 2013)
In today's organizations training is one of the major parts of human resource development (HRD), but training is incomplete until and unless evaluation has taken place, however several previous studies in universal context shows that there is gap in evaluation training programs. In line with this aim, this study had the effort to investigate the perceptions of educational supervisors (ES) concerning current practice in evaluating training programs (ETP) of ES by Ministry of Education (MOE) in Oman. This paper adopted qualitative approach; using multiple- case study design in which data were collected through interviews, also observations and documents review to supplement interview data. The participants in this study were training providers, training evaluators, trainers, direct superiors, and trainees. Data revealed that respondents expressed different views regarding current practice in ETP of ES by MOE, Oman. Most of the interviewees' reflected that existing ETP still not implemented to its full capacity and the appeared that evaluation faced many challenges to get planning, short-terms, and long-terms evaluation resulted; The participants expressed variety recommendations and suggestions to overcome the current weakness and the shortcoming of evaluation performance practice by MOE.